Effects of Phosphorus on Different Genotypes of Wheat and Canola Differing in P-Efficiency in Acidic Soils of Western Australia - Mahdikhani, Mohammadreza; Navaei, Fatemeh; Sadeghi, Kamal (Indonesian Journal of Agricultural Research, 2021)
We hypothesized that phosphorus addition would result in plant morphological changes and changes in rhizosphere carboxylates among wheat and canola cultivars in different acidic soils. Concentration of carboxylates in the rhizosphere extracted with 0.2 mM CaCl2, expressed per unit root dry mass. Dry weight of root and shoot were measures after harvest; total root length, and average root diameter were determined using a scanner. Also, the concentration of phosphorus (Colwell P) in rhizosphere and bulk soil was measured using UV-VIS Spectrophotometer. Shoot and root dry mass of wheat and canola increased significantly with increasing P supply. There was significant difference in total root length and average root diameter between treatments and genotypes in both acidic soils. Citrate was the dominant carboxylate in the rhizosphere of wheat genotypes, and malate was the second one. In canola genotypes, concentration of carboxylates in the rhizosphere were at least 10 times higher than rhizosphere of wheat genotypes. Surprisingly, malonate which there was not in the rhizosphere of wheat genotypes, was the most important carboxylate in the rhizosphere of canola genotypes followed by malate and citrate. This study showed there were significant differences between plant P-efficient and non-efficient in acidic soils when we used different level of P.